2016
DOI: 10.1016/s1470-2045(16)30532-0
|View full text |Cite
|
Sign up to set email alerts
|

Local consolidative therapy versus maintenance therapy or observation for patients with oligometastatic non-small-cell lung cancer without progression after first-line systemic therapy: a multicentre, randomised, controlled, phase 2 study

Abstract: Summary Background Retrospective evidence indicates that disease progression after first-line chemotherapy for metastatic non-small cell lung cancer (NSCLC) occurs most often at sites of disease known to exist at baseline. However, the potential benefit of aggressive local consolidative therapy (LCT) on progression-free survival (PFS) for patients with oligometastatic NSCLC is unknown. Methods We conducted a multicenter randomized study (NCT01725165; currently ongoing but not recruiting participants) to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
824
3
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 945 publications
(899 citation statements)
references
References 28 publications
31
824
3
9
Order By: Relevance
“…Recently, a phase 2 randomized study found that local consolidative therapy with or without maintenance therapy for patients with three or fewer metastases from NSCLC that did not progress after initial systemic therapy improved progression-free survival compared with maintenance therapy alone (41). This study support our findings at some degree, however, we focus aggressive therapy particularly to the primary tumor and patients without treatment before.…”
Section: Subgroup Analysessupporting
confidence: 86%
“…Recently, a phase 2 randomized study found that local consolidative therapy with or without maintenance therapy for patients with three or fewer metastases from NSCLC that did not progress after initial systemic therapy improved progression-free survival compared with maintenance therapy alone (41). This study support our findings at some degree, however, we focus aggressive therapy particularly to the primary tumor and patients without treatment before.…”
Section: Subgroup Analysessupporting
confidence: 86%
“…However, the inclusion of surgical intervention into the treatment strategy for advanced-stage NSCLC has been reproducibly associated with improvements in survival [3][4][5][6][7][8]. Using data from population-based and institutional databases, we and others have demonstrated significantly longer cancer-specific and overall survival in advanced NSCLC patients treated with surgical intervention (alone or in combination) compared with nonsurgical modalities, including chemoradiotherapy, chemotherapy alone, radiotherapy alone, and no treatment (p < 0.001) [3][4][5][6].…”
mentioning
confidence: 87%
“…Survival for advanced-stage NSCLC is only 4%, and outcomes are generally governed by response to systemic therapy [1]. Yet, the inclusion of surgical therapy into multimodality treatment regimens has been reproducibly associated with improved outcomes [3][4][5][6][7][8]15]. A recurrent criticism of these studies is that the observation of improved survival with surgical intervention is attributable to selection bias for patients with favorable characteristics (fewer comorbidities, lower-volume disease) rather the surgical treatment.…”
Section: Commentmentioning
confidence: 99%
“…Recently, in a randomized multicenter phase II clinical trial the issue regarding a right way to manage these patients is correctly answered (9).…”
Section: Editorial On Thoracic Surgerymentioning
confidence: 99%